Gay tourism new perspectives - Vorobjovas-Pinta, Oscar 1987- (Blue Ridge Summit Channel View Publications, 2021)
"This book examines the emerging and shifting issues in the field of gay tourism, how these relate to significant societal and technological changes and the implications of these changes for theory, policy and practice. It will be a useful resource for students, lecturers and researchers in tourism, human geography, cultural studies and sociology"--
Gay tourism: new perspectives -- Gay tourism: political and sociocultural discourses -- Gay tourism: profiles and identities -- Gay tourism: pleasure and leisure -- Gay tourism: spatial discourses
Includes bibliographical references and index.
Keywords: Culture and tourism; Sex tourism; Gay people -- Travel; Sexual minorities -- Travel; Tourism -- Technological innovations